2018
DOI: 10.1002/mc.22939
|View full text |Cite
|
Sign up to set email alerts
|

PPP3CB contributes to poor prognosis through activating nuclear factor of activated T‐cells signaling in neuroblastoma

Abstract: We previously identified a gain‐of‐function mutation in PPP3CB in a neuroblastoma (NB) with MYCN amplification. Here we investigated the functional and clinical role of PPP3CB in NB. High PPP3CB expression was an independent indicator predicting poor prognosis of NB. Overexpression of wildtype or mutated PPP3CB (PPP3CBmut) promoted cell growth, but PPP3CB knockdown decreased cell growth in NB cells. Forced expressions of PPP3CB and PPP3CBmut activated NFAT2 and NFAT4 transcription factors and inhibited GSK3β a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…The analysis results of Kaplan-Meier Plotter and SurvExpress showed that high expression of PPP3CB was associated with worse survival in various tumors such as bladder carcinoma, ovarian cancer, gliomas, and glioblastoma (Figure A3). Similar to the with bioinformatic results, previous research found that high PPP3CB expression was an independent indicator predicting poor prognosis of neuroblastoma (NB) [17]. These results indicate that PPP3CB may be a crucial indicator in the diagnosis or prognosis of cancer.…”
Section: Resultssupporting
confidence: 82%
“…The analysis results of Kaplan-Meier Plotter and SurvExpress showed that high expression of PPP3CB was associated with worse survival in various tumors such as bladder carcinoma, ovarian cancer, gliomas, and glioblastoma (Figure A3). Similar to the with bioinformatic results, previous research found that high PPP3CB expression was an independent indicator predicting poor prognosis of neuroblastoma (NB) [17]. These results indicate that PPP3CB may be a crucial indicator in the diagnosis or prognosis of cancer.…”
Section: Resultssupporting
confidence: 82%
“…Calcineurin-NFATc3 pathway plays a critical role in the pathogenesis of multiple tumors [18,19], which could be activated by calcium. As TRPM8 is a calcium-permeable channel, we speculated PD-L1 might be downstream of TRPM8-calcineurin-NFATc3 pathway.…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known that calcineurin is downstream of calcium signaling, which induces dephosphorylation and activation of transcription factor NFAT [28,29]. Plenty of evidence has reported that calcineurin-NFAT signaling pathway contributes to the development and progression of tumors [18,19,28,29]. Calcineurin is specifically modulated by calcium and calmodulin [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High PPP3CB expression was an independent indicator predicting poor prognosis of neuroblastoma (NB) [38]. PPP3CB contributes to poor prognosis through activating nuclear factor of activated T-cells signaling in NB.…”
Section: Discussionmentioning
confidence: 99%